Linking game-theoretical approaches with constructive type theory : dialogical strategies, CTT demonstrations and the axiom of choice /: dialogical strategies, CTT demonstrations and the axiom of choice. (2015) - Clerbout, Nicolas; Rahman, Shahid, 1956-
No abstract available